2023
DOI: 10.1186/s12906-023-04026-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, antioxidant, and sun protection potential of the isolated compounds from Spermacoce princeae (K. Schum)

Abstract: Background Spermacoce princeae (K. Schum) has been used in the treatment of bacterial skin infections in Uganda. Pharmacological studies revealed that extracts of S. princeae exhibited antibacterial, antioxidant, and sun protection potential. This study aimed at isolating and identifying pure compounds from the extracts based on comprehensive analytical characterization by multiple analytical techniques. Methods The plant samples were extracted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Abou-Hussein et al [68] determined that the mixture of brassicasterol and campesterol manifested antiinflammatory activity in vivo. Akintayo [69] and Sekandí et al [70] reported that a mixture of campesterol, β-sitosterol, and stigmasterol exhibited antioxidant, antimicrobial, and sunscreen activities. Hérnandez-Hérnandez et al [71] reported that the mixture of βsitosterol and stigmasterol had antioxidant, antimicrobial, and antifungal activities.…”
Section: Discussionmentioning
confidence: 99%
“…Abou-Hussein et al [68] determined that the mixture of brassicasterol and campesterol manifested antiinflammatory activity in vivo. Akintayo [69] and Sekandí et al [70] reported that a mixture of campesterol, β-sitosterol, and stigmasterol exhibited antioxidant, antimicrobial, and sunscreen activities. Hérnandez-Hérnandez et al [71] reported that the mixture of βsitosterol and stigmasterol had antioxidant, antimicrobial, and antifungal activities.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant, anti-inflammatory, antidiabetic, anticancer, and hepatoprotective effects of lupeol are amply studied [54]. Phytosterols such as stigmasterol and campesterol exert metabolic effects [55], and possess antioxidant, antimicrobial, and photoprotective properties [56]. Gamma-sitosterol is a natural product with antioxidant, antimicrobial, antidiabetic, and photoprotective properties [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Phytosterols such as stigmasterol and campesterol exert metabolic effects [55], and possess antioxidant, antimicrobial, and photoprotective properties [56]. Gamma-sitosterol is a natural product with antioxidant, antimicrobial, antidiabetic, and photoprotective properties [56,57]. Alpha-amyrin is a natural product derived from ursane with antibiofilm properties against methicillin-resistant and vancomycin intermediate-resistant Staphylococcus aureus [58].…”
Section: Discussionmentioning
confidence: 99%